FEATURES OF STRATEGIC PLANNING INNOVATIVE DEVELOPMENT OF THE RUSSIAN FEDERATION - M. Abramova; O. Demenko; S. Manakhov (Вестник университета)
The article submits characteristic of the Russian Federation innovative development planning narrow and broad understanding stages. The analysis of innovative development strategic planning features in the Russian Federation is carried out. Differences between the Strategy of development of science and innovations in the Russian Federation until 2015 and the Strategy of innovative development of the Russian Federation until 2020 are revealed. Development strategies of the separate branches, subsectors, federal districts reflecting innovative development of the Russian Federation are considered